Vision: a web service for face recognition using convolutional network - Akino Archilles; Arya Wicaksana (Universitas Ahmad Dahlan, 2020)
This paper proposes a face recognition module built as a web service. We introduce a novel design and mechanism for face recognition on a web platform and to memorize most recent users for the user. This web service is called Vision and developed using the Flask and TensorFlow deep learning framework. The face recognition process is powered by FaceNet deep convolutional network model. The face recognition process done by Vision could also be utilized for user authentication and user memorization, both done in on a web platform. As a demonstration of concept and viability, in this study, Vision is integrated into a web-based voice chatbot. The testing and evaluation of Vision’s face recognition process show an overall F-score of one for all test scenarios.